Aberrant serum and tissue levels of Beclin1 and mechanistic target of rapamycin (mTOR) proteins in epithelial ovarian cancer. Issue 17 (28th April 2023) - Lu, Huixia; Hu, Hong; Yang, Zhihong; Li, Shaobo
Abstract : Beclin1 and mechanistic target of rapamycin (mTOR) can be used as tumor markers of epithelial ovarian cancer. This study aimed to assess the association of Beclin1 and mTOR expression with clinicopathological and prognostic data in epithelial ovarian cancer patients. Serum and tissue samples from 45 epithelial ovarian cancer patients and 20 controls were analyzed by enzyme-linked immunosorbent assay and immunohistochemistry for Beclin1 and mTOR expression. The online datasets from gene expression profiling interactive analysis (n = 426), Kaplan–Meier plotter (n = 398), cBioPortal (n = 585), and UALCAN (n = 302) were also analyzed. Beclin1 expression was associated with low-grade differentiation ( P = .003), earlier clinical stage ( P = .013), fewer local lymph node metastases ( P = .02) and lower serum Beclin1 level ( P = .001). mTOR expression was associated with high-grade differentiation ( P = .013), advanced clinical stage ( P = .021), ascites ( P = .028), and higher serum mTOR level ( P = .001). The online datasets showed that a high mTOR expression level (HR = 1.44; 95% CI = 1.08–1.92; P = .013) was associated with a poor overall survival of 426 patients. Beclin1 was mutated in 1.8% and mTOR was mutated in 5% of epithelial ovarian cancer patients. Serum Beclin1 and mTOR levels were able to predict tumor differentiation, clinical stage, lymph node metastasis, and ascites in epithelial ovarian cancer patients.